1975
DOI: 10.1111/j.1471-0528.1975.tb00701.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of Propranolol in Dysfunctional Labour

Abstract: Summary Labour pains associated with fear and anxiety increase the blood level of catecholamines. This in turn causes dysfunctional labour due to the weak uterine contractions which follow stimulation of uterine adrenergic beta receptors. Intravenous propranolol was administered to ten primigravidae with typical dysfunctional labour. This was shortly followed by normal uterine activity and delivery without any significant maternal or fetal complications. To the best of our knowledge this is the first attempt t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1978
1978
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…When the drug was administered intravenously just before induction of anaesthesia for elective Caesarean section, most of the newborn infants were found to have transient respiratory depression (Tunstall, 1969). Studies in animals and man (Amy and Karim, 1974;Barden and Stander, 1968;Mitrani et al, 1975;Shabanah et al, 1968) have shown that propranolol, administered parenterally, increases uterine muscle tone and this could have adverse effects on the fetus. When sheep fetuses received propranolol intravenously and then had their umbilical cords occluded, a fall, instead of the usual rise, was noted and the propranololtreated sheep fetus also failed to get rebound tachycardia which normally occurs after the end of cord compression (Joelsson and Barton, 1969).…”
Section: Discussionmentioning
confidence: 99%
“…When the drug was administered intravenously just before induction of anaesthesia for elective Caesarean section, most of the newborn infants were found to have transient respiratory depression (Tunstall, 1969). Studies in animals and man (Amy and Karim, 1974;Barden and Stander, 1968;Mitrani et al, 1975;Shabanah et al, 1968) have shown that propranolol, administered parenterally, increases uterine muscle tone and this could have adverse effects on the fetus. When sheep fetuses received propranolol intravenously and then had their umbilical cords occluded, a fall, instead of the usual rise, was noted and the propranololtreated sheep fetus also failed to get rebound tachycardia which normally occurs after the end of cord compression (Joelsson and Barton, 1969).…”
Section: Discussionmentioning
confidence: 99%
“…Cesarean section rate was significantly lower in the propranolol group without maternal and neonatal side effects 16 . The first uncontrolled study on the use of propranolol in dysfunctional labor that was done about four decades ago, reported some promising results 17 . Sanchez-Ramos et al compared the effect of oxytocin plus intravenous propranolol infusion with oxytocin plus placebo in abnormal active phase of labor.…”
Section: Propranololmentioning
confidence: 99%
“…Oxprenolol, 1-[(methylethyl)amino]-3-[2-(2-propenyloxy)phenoxy]-2-propanol, is a nonselective b blocker recognized as being an important drug and usually prescribed for the treatment of hypertension, angina pectoris, migraine, and dysfunctional labor (1)(2)(3). Most assay methods for oxprenolol available in the literature are suitable for its determination in biological fluids such as serum and urine (4)(5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%